An instrument to facilitate value-driven conversations on surveillance technology - Gaans-Riteco, Daniëlle van (Nursing ethics, 2025)
BackgroundThe application of care technology is complex, and has an impact on all stakeholders. A specific issue with surveillance technologies is the resulting ethical dilemmas. These dilemmas often touch on people’s values, which arise from their perspectives and determine their attitudes and behaviour. One of the prerequisites for successful stakeholder involvement is knowing and acknowledging their values. Schwartz’s theory of human values has been empirically tested and facilitates the prediction of attitudes and behaviours in different contexts.Research aimTo develop, test and validate a conversation instrument suitable for use in interviews to explore stakeholders’ values regarding the application of surveillance technologies. The instrument was based on Schwartz’s ten values model and adapted to fit the stakeholders’ (professional) backgrounds, education and language levels.Research designWe integrated and adapted Schwartz’s ten and nineteen values model, the Personal Value Dictionary, the Portrait Values Questionnaire and Schwartz’s Value Survey to value cards tailored to the stakeholders’ education and language levels. The adaption was an iterative process involving expert consultation. The value cards were validated in 34 interviews with stakeholders involved in the application of surveillance technologies for people with dementia in nursing homes.Ethical considerationsThis study was approved by the Ethical Research Board of Tilburg University (ID TSB_RP771).FindingsThe iterative process resulted in a concept version of the value cards, with expert feedback and ‘member checks’ guiding final revisions. The value cards helped participants articulate their values and were seen as useful tools for reflecting on key considerations related to surveillance technologies.Discussion and conclusionValue cards assisted stakeholders in sharing their most important principles regarding the application of surveillance technologies and may help explore their values related to complex technological innovations in the context of psychogeriatrics.